2021
DOI: 10.1111/1440-1703.12273
|View full text |Cite
|
Sign up to set email alerts
|

Macroalgal and mangrove provenances demonstrate their relevance in contributing to the blue carbon pool of a tropical seagrass meadow

Abstract: Mangroves, seagrasses and macroalgae form inter-connected coastal habitats.They are involved in the direct and indirect sequestration and accumulation of blue carbon and are recognized for their role in climate change mitigation.Macroalgae, though residing within or in close proximity to these ecosystems are, however, not perceived as contributing to blue carbon storage. Such habitat connectivity among the mangrove, seagrass, and macroalgal compartments complicates a straightforward assessment of blue carbon s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…There is evidence that some of the seaweed detritus material ends up in the deep ocean, it has been observed in the deep sea below 1000 m (Krause‐Jensen & Duarte, 2016). Taking sediment core samples in the deep sea, gives insight on the amount of seaweed derived carbon and existence in the deep sea (Hidayah et al, 2022; Rose & Hemery, 2023; Santos et al, 2019), but these samples do not indicate where the carbon originated and what the ratio of sequestration per biomass would be. Ortega et al (2019) conclude that macroalgae transport to the deep sea takes, place, based on eDNA analysis.…”
Section: Can the Contribution To Climate Mitigation Be Quantified?mentioning
confidence: 99%
“…There is evidence that some of the seaweed detritus material ends up in the deep ocean, it has been observed in the deep sea below 1000 m (Krause‐Jensen & Duarte, 2016). Taking sediment core samples in the deep sea, gives insight on the amount of seaweed derived carbon and existence in the deep sea (Hidayah et al, 2022; Rose & Hemery, 2023; Santos et al, 2019), but these samples do not indicate where the carbon originated and what the ratio of sequestration per biomass would be. Ortega et al (2019) conclude that macroalgae transport to the deep sea takes, place, based on eDNA analysis.…”
Section: Can the Contribution To Climate Mitigation Be Quantified?mentioning
confidence: 99%
“…Ecosystem connectivity can influence blue carbon dynamics because these BCEs can receive OC from upland forest as well as exchange OC among themselves (MacKenzie et al, 2021; Sasmito et al, 2020). The second paper in this special feature by Hidayah et al (2022) found that macroalgal and mangrove‐derived OC are important contributors to seagrass OC sequestration and OC stocks (Hidayah et al, 2022). Understanding the influence of coastal environmental settings on as well as the quantification of allochthonous supplies of organic matter, mineral sediment, and nutrients is an important gap in the storage and sediment OC sequestration potential.…”
mentioning
confidence: 99%
“…Mangrove, seagrass, coral (Adame et al, 2012;Briand et al, 2015;Hernández et al, 2022;León-Pérez et al, 2023;Middelburg et al, 1996;Signa et al, 2017) Mangrove, seagrass (Asplund et al, 2021;Dahl et al, 2022;Hidayah et al, 2022;Kammann et al, 2022;A. K. Mishra et al, 2023;Sullivan et al, 2021;Walton et al, 2014) Mangrove, coral (Keyes et al, 2019) Mangrove (Agraz-Hernández et al, 2018;Analuddin et al, 2021;Feller et al, 2015;Gillis et al, 2016;Moroyoqui-Rojo et al, 2015;Vaiphasa et al, 2007;Williams et al, 2013) Seagrass (Apostolaki et al, 2012;…”
Section: Carbon Stocks and Nutrientsunclassified
“…From the sea side, organic carbon and nutrients can also be imported by seaweed (Hidayah et al, 2022), or in the form of sargassum brown tides resulting from largescale anthropogenic enrichment of continental rivers and offshore areas (Djakouré et al, 2017). This phenomenon, which began in 2011 and has occurred yearly since then, involves the influx of sargassum algae (Oyesiku et al, 2014;Sissini et al, 2019;Van Tussenbroek et al, 2017).…”
Section: Nutrient Enrichmentmentioning
confidence: 99%